2003
DOI: 10.1016/s1063-4584(02)00348-5
|View full text |Cite
|
Sign up to set email alerts
|

Malondialdehyde oxidation of cartilage collagen by chondrocytes

Abstract: These observations suggest that collagen hydroxylation of matrix by vitamin C does not play a role in this model of chondrocyte-dependent collagen degradation. Also, this study demonstrates that chondrocyte-derived lipid peroxidation product MDA mediates oxidation of cartilage collagens. Oxidative modification of cartilage collagen in vivo could result in alteration of biochemical and biophysical properties of cartilage collagen fibrils, making them prone to degradation, thus initiating the changes observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 39 publications
2
26
0
1
Order By: Relevance
“…A series of antioxidants, such as vitamin C (Tiku et al 2003), vitamin E (Bhatti et al 2013), and sodium ferulate (Shang et al 2009), have been demonstrated their chondro-protective properties, as well as potentials in reducing apoptosis and senescence. Cartilage specific proteins including collagen type II and aggrecan can also be elevated after treatment with these agents (Bhatti et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A series of antioxidants, such as vitamin C (Tiku et al 2003), vitamin E (Bhatti et al 2013), and sodium ferulate (Shang et al 2009), have been demonstrated their chondro-protective properties, as well as potentials in reducing apoptosis and senescence. Cartilage specific proteins including collagen type II and aggrecan can also be elevated after treatment with these agents (Bhatti et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Using this model, we showed that chondrocyte-derived lipid peroxidation mediates collagen degradation and that vitamin E inhibits this degradation process (28). More recently, we demonstrated that malondialdehyde (MDA), a toxic aldehydic end product of lipid peroxidation, mediates the oxidation of cartilage collagen (29). MDA and hydroxynonenal (HNE) are specific and major aldehydic products of lipid peroxidation that are believed to be largely responsible for the cytopathologic effects observed during the oxidative stress of lipid peroxidation (23,24).…”
mentioning
confidence: 99%
“…The unique distribution of lipids in cartilage, which changes significantly with age, and dietary intake of lipids could influence the lipid peroxidizability of cartilage. It is possible that alteration in lipid metabolism and oxidative stress could be a catalyst for cartilage aging (Tiku et al 2003). Age-related changes in the lipid composition of cartilage could push the normally contained lipid peroxidation process into a state of uncontrolled oxidative stress, leading to the oxidation of cartilage collagen.…”
Section: Discussionmentioning
confidence: 99%